Optimizing spatial survey administration adopting RT-GSCS: A statistical perspective on performance metrics - Calleo, Yuri; Pilla, Francesco (MethodsX, 2024)
The Real-Time Geo-Spatial Consensus System (RT-GSCS) is a web-based open-source tool designed for the administration of real-time spatial surveys. One distinguishing feature of this system lies in the adoption of the Real-Time Spatial Delphi logic as the main computational algorithm to achieve a convergence of opinions within a group of individuals. The system is available at http://rtgscs.com/ and is particularly instrumental in supporting the decision-making process when spatial data is absent or when user judgments are solicited for territorial actions. Since the release of the beta version, the system has undergone multiple iterations and significant changes, and for this reason, an updated assessment should be conducted. In this paper, we present an in-depth exploration of the latest version of RT-GSCS (v3.0), which includes novel algorithms, statistical analysis, and spatial techniques, optimized for survey administration. The analysis is meticulously conducted by evaluating a comprehensive array of parameters, encompassing performance metrics, spatial elements, security, updates, and privacy assessments. Moreover, a thorough examination of user feedback is presented, enriching the depth of our investigation. This mixed-method approach ensures a robust and updated investigation of the system, facilitating a nuanced comprehension of the process and the attainment of spatial consensus.•Existing spatial survey administration systems cannot facilitate group collaboration for achieving a spatial consensus on the territory in real-time.•The RT-GSCS experienced substantial modifications, necessitating a revised technical evaluation from the initial beta version to its current version.•The proposed method fills the gaps of a technical performance evaluation of the latest version of RT-GSCS, useful for achieving a spatial consensus among a group of individuals with an assessment of the overall performances. [Display omitted]